The Effect of the Inquiry Learning Model on Students’ Metacognition Awareness - Samsun Hidayat; Muhammad Asy'ari; Muhali Muhali; Roniati Sukaisih (Universitas Pendidikan Mandalika, 2019)
This study aims to determine the effect of inquiry learning models on the students’ metacognition awareness in senior high school. Metacognition awareness in this study consists of eight components, namely (1) declarative knowledge, (2) procedural knowledge, (3) conditional knowledge, (4) planning, (5) information management system, (6) monitoring, (7) evaluation, and (8) debugging. This research is a quasi-experimental research with one group pretest-posttest design. The sample in this study were 25 students of science in Madrasah Aliyah Negeri 3 Lombok Tengah chosen using the saturated sample technique. Metacognition Awerness Inventory (MAI) is used to collect metacognition awareness data of students who are analyzed using paired t-test and Wilcoxon test samples. The results showed that students' metacognition awareness for all indicators was stated to increase (p <0.05) after learning using inquiry learning models. Based on these results, it can be concluded that the inquiry learning model influences the metacognition awareness of secondary school students.